Advertisements And Different Types Of Promotions Used In Mobile Telephone: A Case Study On Maxis Communication Berhad - Pour, Arash Hossein (2007)
After briefly discussing some background on mobile marketing, the paper conceptualizes key characteristics for mobile marketing permission and acceptance. Finally key success factors for mobile marketing are discussed.